Research on Environmental Protection Strategy of Urban Construction Subject Based on Evolutionary Game - Liu, Mengkai; Zhang, Shujie (Sustainability, 2022)
With the urban renewal and development, the impact of urban construction projects such as old city reconstruction on the surrounding environment has always attracted social attention in the construction process. The strategies of the participants in the project construction in the process of environmental protection need to be further clarified. Taking the government investor and contractor as the construction subject, combined with questionnaire survey and evolutionary game, determines the three-party evolutionary stable game strategy and clarifies the internal mechanism of the evolution trend of the construction subject through simulation. The results show that the investor and contractor have a certain awareness of environmental protection, but they have limited understanding of the relevant policies and regulations issued by the government and believe that the government has little supervision and governance. The optimal evolutionary stability strategy adopted by the construction subject in promoting environmental protection is {Incentive, Effective supervision, Proper protection}, in which the stability conditions are J1 > M1 and T1 > N1. Reducing G1, A, M1, N1 and T1 or increasing J1 and the construction subject’s willingness to take measures can promote the model to stabilize and evolve. The government should establish and improve the incentive system, improve the environmental protection awareness of the construction subject, urge the investor and the contractor to take effective measures to achieve the long-term stability goal of the tripartite subject strategy, and minimize the impact on environmental protection.